PENGEMBANGAN BUKU CERITA REMAKE SATUA BALI PAN BALANG TAMAK BERORIENTASI RESPONSIBLE DECISION MAKING UNTUK SISWA SD - Yoga Sedana Kori, Made; Nanci Riastini, Putu; Kusuma Widiastuti, Ni Putu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limited reinforcement of responsible decision-making skills among elementary school students is caused by learning practices that remain cognitively oriented and the lack of contextual and local culture-based teaching materials. On the other hand, satua Bali, which is rich in moral values, has not been optimally utilized due to its conventional presentation and limited relevance to the lives of today’s digital generation students. This study aimed to develop a remake storybook of the Balinese folktale entitled Pan Balang Tamak, as well as to determine the validity and practicality of the developed storybook for elementary school students. This research employed a development research design using the ADDIE model, which consists of five main stages: analysis, design, development, implementation, and evaluation. Data was collected through a relevance scale to assess content validity and questionnaires to obtain user responses. The collected data were analyzed using quantitative and qualitative analysis techniques. The results of the content validity test indicated a very high category, with scores of 1.00 from the material expert, 1.00 from the media expert, and 0.9 from the language expert. The feasibility of the book as a learning resource was also supported by teacher responses, which reached 97.33% (very good qualification), and student responses, which reached 95.76% (very good qualification). Based on these findings, it can be concluded that the developed remake storybook demonstrates a very high level of validity and practicality for use as a learning resource for elementary school students. The implications of this study indicate that the remake storybook Pan Balang Tamak can support the strengthening of cultural literacy and students’ character development, particularly in responsible decision making, when supported by collaboration between schools and the government in integrating traditional values into modern learning contexts.